Unsettled Urban Space Routines, Temporalities and Contestations - Viderman, Tihomir; Knierbein, Sabine; Kränzle, Elina; Frank, Sybille; Roskamm, Nikolai; Wall, Ed (Taylor & Francis, 2023)
While urban life can be characterized by endeavors to settle stable and safe environments, for many people, urban space is rarely stable or safe; it is uncertain, troubled, imbued with challenges and perpetually under pressure. As the concept of unsettled appears to define the contemporary urban experience, this multidisciplinary book investigates the conflicts and possibilities of settling and unsettling through open and speculative analysis. The analytical prism of unsettled renders urban space an indeterminate ground unfolding through routines, temporalities and contestations in constant tension between settling and unsettling. Such contrasting experiences are contingent on how urban societies confront, undergo and overcome turbulence and difficulties in time and space. Contributions drawing on theoretical reflections and empirical accounts-from Argentina, Austria, Germany, Greece, Italy, the Netherlands, the UAE, the UK, the USA and Vietnam-give insights into plural occurrences of the unsettled, which might tie down or unleash transformative, liberatory and emancipatory potentials. This book is for students, professionals and researchers interested in the uncertainties, foundations, disturbances, inconsistencies, residuals and blind fields, which constitute the urban both as lived space and as social, cultural and political ideal.